Психологічне здоров'я як чинник гармонійного розвитку сучасної української молоді - Підбуцька, Ніна Вікторівна; Курявська, Олена Миколаївна (НТУ "ХПІ", 2011)
In the article consistently reviewed various approaches to the study of psychological health. On the basis of the literature analysis the criteria of psychologically healthy person. Revealed the need for psychological health as an integral component of personal development. An experimental investigation of the psychological health of the modern youth.
Keywords: психологічне здоров'я; соціальні потреби; самоактуалізація особистості; психологічні можливості